Genetic effects of Spodoptera frugiperda resistance in maize lines derived from germplasm native of Tamaulipas - Reséndiz Ramírez, Zoila; López Santillán, José Alberto; Estrada Drouaillet, Benigno; Osorio Hernández, Eduardo; Pecina Martínez, José Agapito; Mendoza Castillo, ,Ma. del Carmen (Revista Mexicana de Ciencias Agrícolas, 2017)
The fall armyworm (Spodoptera frugiperda) damage maize throughout the life cycle of the plant; one option for this problem is the development and use of resistant cultivars; for this, it is necessary to know the genetic behavior of the characteristics that induce this resistance. S. frugiperda resistance was genetically evaluated by no preference of maize cultivars developed with germplasm native of Tamaulipas; in the autumn-winter cycle 2014- 2015, in Güémez, Tamaulipas, in fertilization and nonfertilization treatments, six inbred maize lines derived from native germplasm, its direct and reciprocal crosses and four commercial hybrids were evaluated in a complete random block design; a diallel analysis was performed to determine maternal, reciprocal, general and specific combinatorial effects; leaf damage by S. frugiperda was estimated in the stages of the sixth ligulate leaf (DFH6), tenth (DFH10) and flowering (DFHF). There was minor damage of S. frugiperda in the fertilization treatment compared to the non fertilization one; also statistical differences between cultivars for DFH6 and significant interaction between cultivars and fertilization treatments. PWL1S3×PWL6S3 y TGL2S3×LlHL5S3 crosses had negative effects of specific combining ability; the first showed significant reciprocal effects due to maternal effects of the PWL1S3 line, this shows that the variation for this feature is explained by maternal effects and no additives; additionally DFH6 of S. frugiperda of 0.867 showing lower preference of the insect in comparison to the rest of the cultivars.
Keywords: Zea mays L., combining ability, diallel, fall armyworm